Relações lineares funcional e estrutural sujeitas a erros de observação - Prado, Bárbara Brandao de Almeida (1980)
In practice often occur situations in which physicists, chemists, biologists, engineers and others beliEve in the existence of mathematical relationships between variables they deal with, although these relationships are obscured by "random fluctuations", associated to all variables. In this thesis, we intend to examine all the possible situations originated by a pair of random variables, when errors of measurement "controlled or not" by the experimenter, are present